1995
DOI: 10.1111/j.1432-1033.1995.tb20738.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Sequence and mRNA Tissue Distribution of a Novel Human Matrix Metalloproteinase with a Potential Transmembrane Segment

Abstract: The complementary DNA sequence of a novel matrix metalloproteinase was isolated from a human lung cDNA library. It consists of 3530 bp and encodes a polypeptide of 669 amino acids. In comparison to other matrix metalloproteinases, the deduced sequence of the amino acid chain exhibits closest similarity to a recently discovered membrane-type matrix metalloproteinase of 582 amino acids. Likewise, it is composed of a signal peptide, a prodomain, a catalytic domain, a hemopexin-homologous domain and a C-terminal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0
6

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(102 citation statements)
references
References 21 publications
1
95
0
6
Order By: Relevance
“…They consist of collagenases, gelatinases, stromelysins (Birkedal-Hansen et al 1993), matrilysin (MMP-7) (Woessner and Taplin 1988;Quantin et al 1989) and matrix metalloelastases (MMP-12) (Shapiro et al 1993), and membrane-type matrix metalloproteinases (MT-MMPs) (Sato et al 1994;Will and Hinzmann 1995;Hernandez-Barrantes et al 2002). MMPs are known to be important in embryonic development, tissue morphogenesis and repair, inflammation and cancer (Nelson et al 2000;Sternlicht and Werb 2001).…”
Section: Introductionmentioning
confidence: 98%
“…They consist of collagenases, gelatinases, stromelysins (Birkedal-Hansen et al 1993), matrilysin (MMP-7) (Woessner and Taplin 1988;Quantin et al 1989) and matrix metalloelastases (MMP-12) (Shapiro et al 1993), and membrane-type matrix metalloproteinases (MT-MMPs) (Sato et al 1994;Will and Hinzmann 1995;Hernandez-Barrantes et al 2002). MMPs are known to be important in embryonic development, tissue morphogenesis and repair, inflammation and cancer (Nelson et al 2000;Sternlicht and Werb 2001).…”
Section: Introductionmentioning
confidence: 98%
“…4. Membrane-type matrix metalloproteinases (MTMMPs) make up a new subclass and include MT-MMP-1, -2, and -3 (Sato et al 1994;Will and Hinzmann 1995;Takino et al 1995). These MT-MMPs are localized at cell surfaces and their substrate specificities are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced expression of proM-MP-2 has also been reported in the articular cartilage of human osteoarthritis (Martel-Pelletier et al 1994). In addition to soluble MMP, a family of membrane typematrix metalloproteinases (MT-MMP) has also been described (Will and Hinzmann 1995). Various studies have demonstrated the presence of MTl-MMP in a variety of human carcinoma cells and in their stromal cells (Okada et al 1995;Gilles et al 1996).…”
Section: Introductionmentioning
confidence: 99%